Kopřivnice 3.0 - Bydlení A++ - Lapešová, Tereza (Vysoké učení technické v Brně. Fakulta architektury, 2024)
Předmětem diplomové práce je návrh nové čtvrti ve městě Kopřivnice. Parcela je vlastněna městem. Návrh obsahuje tedy polyfunkční objekt a tři bytové domy. Výstavba je financovaná pomocí PPP - Public Private Partnership mezi městem a soukromníkem. Práce se soustředí převážně na bytové objekty a velká pozornost je kladena na veřejný prostor. Celou Kopřivnící prochází řeka Kopřivnička obklopená zelení, na kterou dané území reaguje. Domy jsou navrženy s myšlenkou na maximální variabilitu a jednoduchou výstavbu.

The diploma thesis focuses on the design of a new district in the town of Kopřivnice. The plot is owned by the municipality. The proposal includes a multifunctional building and three residential buildings. The construction is financed through a Public-Private Partnership (PPP) between the municipality and a private investor. The thesis primarily concentrates on the residential properties with significant attention given to public spaces. The entire area of Kopřivnice is intersected by the Kopřivnička River surrounded by greenery, to which the proposed area responds. The houses are designed with a focus on maximum variability and straightforward construction.
Koprivnice 3.0 - Housing A++
Keywords: Bydlení; dostupnost; variabilita; Public Private Partnership; Kopřivnice; zeleň; Housing; Accessibility; Variability; Public Private Partnership; Kopřivnice; Greenery